AUTOMATIC DISCOVERY OF CANDIDATE IN THE RELATIONAL DATABASES KEYS BY USING ATTRIBUTES SETS CLOSURE - Al-ward, Yasmeen F (Al-Nahrain Journal of Science, 2010)
The automation of database design, design weak points' detection, re-engineering and schemamodification, and normalization of the database systems became the crucial aspects in databasesstudies. In real applications databases the discovery of candidate keys is regarded as a challenge forthe designers. This research proposes an algorithm to automate the discovery of the candidate keysin the databases depending on the attributes set closure and functional dependency, FD, rules. Inthis research, the functional dependency rules are regarded as production rules to product binarystrings which represent the sets of attributes and the candidate keys. Representing the rules and thesets of attributes as binary string allows proposing novel string matching and ordered stringsmerging which linearly speed up the execution time according to the number of attributes and thenumber of functional dependency rules.The proposed system was tested successfully by using many actual and synthesis schemas anddependencies some of these schemas and dependencies include one hundred attributes and onehundred FD rules respectively.